Effect of VEGF on Inflammatory Regulation, Neural Survival, and Functional Improvement in Rats following a Complete Spinal Cord Transection - Li, Jing; Chen, Shuangxi; Zhao, Zhikai; Luo, Yunhao; Hou, Yuhui; Li, Heng; He, Liumin; Zhou, Libing; Wu, Wutian (Frontiers in Cellular Neuroscience, 2017)
After complete transection of the thoracic spinal segment, neonatal rats exhibit spontaneous locomotor recovery of hindlimbs, but this recovery is not found in adult rats after similar injury. The potential mechanism related to the difference in recovery of neonatal and adult rats remains unknown. In this study, 342 animals were analyzed. The vascular endothelial growth factor (VEGF) level in spinal segments below injury sites was significantly higher in postnatal day 1 rats (P1) compared with 28-day-old adult rats (P28) following a complete T9 transection. VEGF administration in P28 rats with T9 transection significantly improved the functional recovery; by contrast, treatment with VEGF receptor inhibitors in P1 rats with T9 transection slowed down the spontaneous functional recovery. Results showed more neurons reduced in the lumbar spinal cord and worse local neural network reorganization below injury sites in P28 rats than those in P1 rats. Transynaptic tracing with pseudorabies virus and double immunofluorescence analysis indicated that VEGF treatment in P28 rats alleviated the reduced number of neurons and improved their network reorganization. VEGF inhibition in neonates resulted in high neuronal death rate and deteriorated network reorganization. In in vivo studies, T9 transection induced less increase in the number of microglia in the spinal cord in P1 animals than P28 animals. VEGF treatment reduced the increase in microglial cells in P28 animals. VEGF administration in cultured spinal motoneurons prevented lipopolysaccharide (LPS)-induced neuronal death and facilitated neurite growth. Western blots of the samples of lumbar spinal cord after spinal transection and cultured spinal motoneurons showed a lower level of Erk1/2 phosphorylation after the injury or LPS induction compared with that in the control. The phosphorylation level increased after VEGF treatment. In conclusion, VEGF is a critical mediator involved in functional recovery after spinal transection and can be considered a potential target for clinical therapy.